Tuning the dimensionality of organometallic–organic hybrid polymers assembled from [Cp2Mo2(CO)4(η2-P2)], bipyridyl linkers and AgI ions12. Issue 46 (14th November 2018) - Elsayed Moussa, Mehdi; Peresypkina, Eugenia; Virovets, Alexander V.; Venus, Dominik; Balázs, Gábor; Scheer, Manfred
Abstract : The first of its kind study of the effect of the organic linker length and reaction temperature on aggregation reactions leading to organometallic–organic hybrid polymers is presented. Abstract : The reactions of the P2 ligand complex [Cp2 Mo2 (CO)4 (η 2 -P2 )] (Cp = C5 H5, 1) with Ag[Al{OC(CF3 )3 }4 ](A g[TEF]) in the presence of the rigid bipyridyl linkers 1, 2-di(pyridin-4-yl)ethyne (3 ), 4, 4′-bis(pyridin-4-ylethynyl)-1, 1′-biphenyl (4 ) and 4, 4′-bipyridine (5 ) possessing various lengths are studied. The reaction with the longer linkers (3 and4 ) leads to the formation of the 1D organometallic–organic hybrid polymers [{Cp2 Mo2 (CO)4 (μ4, η 1:1:2:2 -P2 )}2 {Cp2 Mo2 (CO)4 (μ3, η 1:2:2 -P2 )}2 (μ, η 1:1 -C12 H8 N2 )Ag2 ] n [TEF]2 n (6 ) and [{Cp2 Mo2 (CO)4 (μ4, η 1:1:2:2 -P2 )}2 {Cp2 Mo2 (CO)4 (μ3, η 1:2:2 -P2 )}2 (μ, η 1:1 -C26 H16 N2 )Ag2 ] n [TEF]2 n (7 ) in high selectivity. A similar reaction with the short linker5 affords a mixture of the 2D hybrid polymers [{Cp2 Mo2 (CO)4 (μ4, η 1:2:2:2 -P2 )}2 (μ, η 1:1 -C13 H14 N2 )Ag2 ] n [TEF]2 n (8 ) and the 3D hybrid network [{Cp2 Mo2 (CO)4 (μ4, η 1:1:2:2 -P2 )}2 (μ, η 1:1 -C10 H8 N2 )Ag] n [TEF]2 n (9 ). However, a selective synthesis of8 or9 is possible when the reaction is performed at 0 °C and 60 °C, respectively.